Full-duplex MIMO and PLNC for the Y-network - Ferreira, F. E. (2021)
This paper considers a multi-way wireless network with three terminals which want to exchange or share data with the help of a relay: each terminal has some information that wants to transmit to the other two. The traditional way of doing this exchange either involves time-domain multiplexing (TDMA) or dedicated frequency-domain disjoint channels, at the expense of high bandwidth inefficiency. With the advent of network coding, and later physical-layer network coding, it became possible to reduce the number of time slots required to exchange the information between all the terminals. Moreover, using multiple-input multiple-output (MIMO) terminals and relays, the time-usage efficiency can be further boosted by transferring the burden from the time-domain to the spatial-domain via spatial multiplexing. This paper proposes the concatenation of the aforementioned techniques along with loopback interference cancellation, which recently became a central topic for the next generation of the physical-layer of wireless communications. The paper shows a protocol and techniques that allow all the information exchange between terminals to be reduced from the 6 time-slots, required in traditional TDMA, to one time-slot only, provided that the information packets are not too short. The error performance of this system is shown by means of simulation using MIMO Rayleigh fading channels.